2019
DOI: 10.1262/jrd.2019-037
|View full text |Cite
|
Sign up to set email alerts
|

Human chorionic gonadotropin (hCG)-induced ovulation occurs later but with equal occurrence in lactating dairy cows: comparing hCG and gonadotropin-releasing hormone protocols

Abstract: This study assessed the effects of two hormones, human chorionic gonadotropin (hCG) and gonadotropin-releasing hormone (GnRH), on ovulatory responses during different diestrous stages in lactating dairy cows. Estrous cycles of 21 cows were synchronized and were enrolled in stage 1 of the experiment. The cows were treated with a prostaglandin (PG) F2α analog either 9 to 10 days [mid-diestrus (MD) group] or 5.5 to 6.5 days [early-diestrus (ED) group] after synchronized ovulation (day 0 = first PGF2α administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…By contrast, cows treated in early diestrus (i.e., 5.5-6.5 d after ovulation) ovulated earlier in both treatments (28.8 ± 0.4 h and 32.8 ± 2.2 h for GnRH and hCG, respectively). Independent of the stage of the estrous cycle, cows treated with GnRH ovulated earlier than cows treated with hCG (Liu et al, 2019).…”
Section: Effect Of Treatment On Time To Ovulationmentioning
confidence: 94%
See 2 more Smart Citations
“…By contrast, cows treated in early diestrus (i.e., 5.5-6.5 d after ovulation) ovulated earlier in both treatments (28.8 ± 0.4 h and 32.8 ± 2.2 h for GnRH and hCG, respectively). Independent of the stage of the estrous cycle, cows treated with GnRH ovulated earlier than cows treated with hCG (Liu et al, 2019).…”
Section: Effect Of Treatment On Time To Ovulationmentioning
confidence: 94%
“…Based on a distribution of time from treatment to ovulation (Figure 2), no cows in either treatment ovulated within 24 h after treatment, and there was overlap in time to ovulation between treatments. Liu et al (2019) reported time from treatment to ovulation after treatment of dairy cows with GnRH (250 µg of gonadorelin) and 3,000 IU of hCG to be 29.3 ± 0.5 h and 34.3 ± 2.5 h, respectively (P < 0.01). In that study, ovulation was determined every 2 h from 24 to 36 h after treatment, and treatments were administered intramuscularly during mid or early diestrus.…”
Section: Effect Of Treatment On Time To Ovulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Time from treatment to ovulation may vary among GnRH (gonadorelin) and hCG, depending on the estrous cycle phase when the treatment is administered (Liu et al, 2019;Cabrera et al, 2021b). However, regardless of the estrous cycle phase, cows treated with hCG ovulate later than cows treated with GnRH (gonadorelin; Liu et al, 2019).…”
Section: Hcg Versus Gnrh: Mechanism Of Action and Their Follicular An...mentioning
confidence: 99%
“…Time from treatment to ovulation may vary among GnRH (gonadorelin) and hCG, depending on the estrous cycle phase when the treatment is administered (Liu et al, 2019;Cabrera et al, 2021b). However, regardless of the estrous cycle phase, cows treated with hCG ovulate later than cows treated with GnRH (gonadorelin; Liu et al, 2019). In both studies, the difference in time for ovulation between hCG and GnRH is between 2 and 5 h. It was speculated that the ovulation might occur later after hCG treatment than GnRH because of the delayed time to hCG or LH peak concentration, which is reached 4 h after treatment with hCG (Nascimento et al, 2013) versus 1 to 2 h after treatment with 4 different GnRH analogs (Souza et al, 2009;Giordano et al, 2012).…”
Section: Hcg Versus Gnrh: Mechanism Of Action and Their Follicular An...mentioning
confidence: 99%